Glutaredoxins are essential for stress adaptation in the cyanobacterium Synechocystis sp. PCC 6803 - Sánchez-Riego, Ana M.; López-Maury, Luis; Florencio, Francisco J. (Frontiers in Plant Science, 2013)
Glutaredoxin are small redox proteins able to reduce disulfides and mixed disulfides between GSH and proteins. Synechocystis sp. PCC 6803 contains three genes coding for glutaredoxins: ssr2061 (grxA) and slr1562 (grxB) code for dithiolic glutaredoxins while slr1846 (grxC) codes for a monothiolic glutaredoxin. We have analyzed the expression of these glutaredoxins in response to different stresses, such as high light, H2O2 and heat shock. Analysis of the mRNA levels showed that grxA is only induced by heat while grxC is repressed by heat shock and is induced by high light and H2O2. In contrast, grxB expression was maintained almost constant under all conditions. Analysis of GrxA and GrxC protein levels by western blot showed that GrxA increases in response to high light, heat or H2O2 while GrxC is only induced by high light and H2O2, in accordance with its mRNA levels. In addition, we have also generated mutants that have interrupted one, two or three glutaredoxin genes. These mutants were viable and did not show any different phenotype from the WT under standard growth conditions. Nevertheless, analysis of these mutants under several stress conditions revealed that single grxA mutants grow slower after H2O2, heat and high light treatments, while mutants in grxB are indistinguishable from WT. grxC mutants were hypersensitive to treatments with H2O2, heat, high light and metals. A double grxAgrxC mutant was found to be even more sensitive to H2O2 than each corresponding single mutants. Surprisingly a mutation in grxB suppressed totally or partially the phenotypes of grxA and grxC mutants except the H2O2 sensitivity of the grxC mutant. This suggests that grxA and grxC participate in independent pathways while grxA and grxB participate in a common pathway for H2O2 resistance. The data presented here show that glutaredoxins are essential for stress adaptation in cyanobacteria, although their targets and mechanism of action remain unidentified.